The Future Buddhist Education Development in Indonesia: Reconstruction of Buddhism Views and Advocating for the Buddhayāna Spirit Movement to Integrate into Indonesian Buddhist Education - Nyanabhadra, Phap Tu; Sutawan, Komang; Susanto, Susanto; Tang, Troi Bao (LPPM STIAB JINARAKKHITA LAMPUNG, 2025)
Buddhist education in Indonesia faces significant challenges and opportunities in future developments, especially in integrating spiritual values with the demands of modern times. This review and study analyzed the dynamics of the development of Buddhist education by reconstructing the Buddhist community's view of religious education and the advocacy efforts of the Buddhayāna spirit movement. This approach emphasizes building a collective consciousness oriented towards universal human wisdom and values. The reconstruction of the Buddhist community's view includes the transformation of the traditional paradigm towards a more inclusive, relevant, and adaptive approach to the needs of the millennial generation and the digital generation. In addition, the Buddhayāna spirit movement was introduced as an integrative strategy to bridge traditional Buddhism with modern education in both formal and informal realms. This movement emphasizes the importance of curriculum reform, the development of technology-based learning methods, and the strengthening of Buddhist ethical values in creating a generation that is not only intellectually intelligent but also wise and with integrity. The results of the analysis show that collaboration between religious stakeholders, government, and society is the key to the success of Buddhist education in the future. Applying the Buddhayāna spirit is expected to strengthen the position of Buddhist education in supporting inclusive and harmonious nation-building. Therefore, this research provides a strategic and practical perspective to advance Buddhist education in Indonesia through an innovative, integrative, and relevant approach to the existing socio-cultural context.